CREATING QUALITY TEACHING MATERIAL FOR ENGLISH CLASSES IN PUBLIC SCHOOLS (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2023)
The use of pedagogical material is a very important tool for our teaching practice. In this study we reflect on how the creation of quality pedagogical material enhances English teaching at the Residência Pedagógica Program (PRP)- Núcleo de Língua Inglesa of the Universidade Federal do Pampa (Unipampa), campus Bagé/RS. As CAPES scholarship holders, we plan and teach English lessons at two public schools in BagéLuis Mércio Teixeira High School, a State school, and General Emílio Luiz Mallet Middle School, a City school. Here, we argue that our job is to provide students with interesting and quality materials. Well-designed teaching materials ensure consistency and coherence in teaching. This is particularly useful in language classes, so that the students can always feel motivated. Using learning materials helps to align students' learning expectations and ensures that everyone receives consistent, quality instructions. Knowing how to use and choose materials for the class is something we learned in this experience as residents of English. We should look for ways and strategies to make the class clearer and more objective for the students, and to ensure that each student learned correctly, so that there are no doubts. Varied resources and activities make the class more motivating and interesting. A good teaching material offers a variety of resources and activities that can be used by the teacher in the classroom. This includes vocabulary exercises, grammar practices, readings, audios and videos, games, and interactive activities. This variety allows the teacher to diversify activities and meet the needs of different learning styles (ZAMBON, 2013). At Luis Mércio High School, our first impression was that students did not identify with the English language. However, according to Nascimento (2009), language is a social construct, it inherently expresses the cultural characteristics of its users, whether they are native speakers or not. In order to connect with students in terms of culture and language use, it is necessary to identify their sociocultural environment. Because of that, we looked for methodologies that went beyond textbooks and allowed students to look at the additional language from another perspective. Developing our own teaching materials, we thought of topics that could talk to the students, such as graphite, bullying in schools, and Anne Frank among others. The didactic material can serve as a valuable guide for planning lessons. We could see that there were a lot of resources available and we needed to be careful about what to choose (POLIDÓRIO, 2014). Materials can provide clear learning objectives, suggested activities and teaching strategies, and offer ideas for assessment and feedback. The feedback to students was made easier, because they could already understand their difficulties with the support of the teaching materials since materials can make students feel comfortable to receive corrections and feedback in a positive way. Choosing materials that catch the attention of students makes them interact and engage more actively. At Emílio Luiz Mallet Middle School, we value class time. We noticed that students wasted time copying extensive content from the board that they often would not remember or revise after the class ended. Quality teaching material helps the students build an affective memory with the content worked on. This affective memory happens when diverse colors, shapes, sizes, images take over and relate to other memories and feelings. In the eighth and ninth grade classes, we had activities with music, games always using the didactic resource as a support to carry out the exercises. The students always said how much the "sheet of papers" helped them to carry out the activities. Even if the students do not keep the activity sheet of paper, they manage to learn the content cognitively while in class. For that reason, only writing the content and the activities on the board will not suffice. It endangers the learning process. Quality and up-to-date materials, with colorful images or illustrations, help teaching to be based on best practices and the latest trends. In our experience, as residents of PRP, the use of didactic material brought us confidence and quality in teaching English (FISCARELLI, 2007). The didactic material provides a clear and objective teaching structure and sequence so that the student can accomplish the task they are challenged with. We could observe that with a script for the classes, our classes became more organized, consistent and followed a certain progression week after week. When we are building our identity as English teachers, it is important to use teaching resources and powerful materials that bring excellent quality to the class in terms of activity variety and also design that trigger affective and cognitive responses from the students.